Implikasi Kompetensi Pedagogis terhadap Hasil Belajar Siswa dan Kinerja Guru - Nur Cholisoh; Sri Rezeki; Deden Ibnu Aqil (LITERATUS, 2020)
The purpose of this study was to determine the effect of pedagogical competence on learning outcomes and teacher performance. The school that is the object of this research is the Tri Ratna School, West Jakarta. The method used in this research is a survey method with a correlational approach to see if there is an influence between the independent variable (Teacher Competence) and the dependent variable (Teacher Performance). The results showed that there was a significant influence between teacher competence and teacher performance at Tri Ratna School, West Jakarta and student learning outcomes at SMK Daarul Mannan Bekasi.